Sequential Organocatalytic Synthesis of [1, 2, 3]Triazolo[1, 5‐a]quinolines. Issue 22 (16th October 2020) - da Costa, Gabriel P.; Bach, Mariana F.; de Moraes, Maiara C.; Barcellos, Thiago; Lenardão, Eder J.; Silva, Márcio S.; Alves, Diego
Abstract: In this work, a one‐pot sequential organocatalytic method for the synthesis of fused [1, 2, 3]triazolo[1, 5‐ a ]quinolines through successive cyclization and condensation is presented. In this synthetic strategy, the intermolecular [3+2]‐cycloaddition occurs between 1, 3‐dicarbonyl compounds and o ‐carbonyl‐substituted phenylazide compounds, for the formation of the 1, 2, 3‐triazole intermediates. Subsequently, an intramolecular condensation reaction generates the fused quinoline ring by the new C−C bond formation, giving the products in yields ranging from moderate to excellent. All the reactions were performed using 20 mol% of 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) as catalyst in the presence of DMSO as solvent at 120 °C for 24 h and tolerate a range of 1, 3‐dicarbonyl compounds, such as β ‐keto esters and 1, 3‐diketones, and o ‐formyl, o ‐acetyl or o ‐benzoyl substituted phenylazide compounds. Abstract :